Peran Mahasiswa KKN Dalam Branding Dan Promosi Wisata Embung Sumberagung Kecamatan Gondang - Merlina Aris Fitria Dewi; R. Yuniardi Rusdianto (Fakultas Teknik Universitas Cenderawasih, 2023)
In the tourism village scheme, KKN students focus their work program in Sumberagung Village, Gondang District, Nganjuk Regency on developing tourism potential. One of the tourism potentials in Sumberagung Village is embung or reservoir. In developing the tourism potential of Embung Sumberagung, KKN students conduct branding and promotion for the tour. The implementation of this activity is carried out using the participation method where KKN students actively participate and take the initiative in branding and promoting Embung Sumberagung tourism. With the branding and promotion of Embung Sumberagung tourism, it can add information to the community or tourists so that this tourism potential can be known by a wider community.